Analysis on the CTLM and LTLM applicability for GaN HEMTs structure alloyed ohmic contact resistance evaluation - Lin, Shuxun; Meng, Di; Wen, Cheng P.; Wang, Maojun; Wang, Jinyan; Hao, Yilong; Zhang, Yaohui; Lau, Kei May (2013 IEEE INTERNATIONAL CONFERENCE OF ELECTRON DEVICES AND SOLID-STATE CIRCUITS (EDSSC), 2013)
In this letter, we have demonstrated that the circular transmission linear model (Marlow's CTLM) is unsuitable for GaN HEMTs structure alloyed ohmic contact resistance evaluation. Very large spread is found in the extracted ohmic resistance values from measured data using the commonly used CTLM test patterns, and some of the contact resistances are found to be negative. We suspect that the stress induced by ohmic contact formation process is the culprit, preventing the use of CTLM test pattern for GaN HEMTs structure ohmic contact resistance evaluation, because of the strong piezoelectric induced polarization property of the hexagonal Ill-nitride heterojunction device structure. Meanwhile, measured ohmic contact resistance (R-c) and sheet resistance (R-sq) are found to exhibit good uniformity using a properly prepared linear transmission line model (LTLM) test pattern in which all the Gallium nitride material extended beyond the gaps between the ohmic contact electrodes are removed.